Funding Science in Ukraine: Directions for Change - A. Sokolovska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article explores ways of reforming mechanism of funding science in Ukraine and substantiates the requirement to grant subsidies for research and development to the universities on the base of top ranks in research, technical and innovative activates. Basic funding of academic science and research should be improved by splitting the fund structure into a fixed and variable part, which will be determined by the National Academy of Sciences on the base of assessing effectiveness of the academic institutions. It is proposed to ensure a gradual increase of the variable part of funding from 10 to 30% of the total amount and allocate it among institutions according the formula based on the indicators of research activity. In order to increase the competitive funding of science through the National fund of researches of Ukraine, the ways are suggested to improve tax incentives for attracting voluntary contributions of legal entities and individuals to the budget of the Fund.